EFEKTIVITAS KEBIJAKAN SATU PINTU PENGELOLAAN LIMBAH BAHAN BERBAHAYA DAN BERACUN PADA PT. KALTIM PRIMA COAL EFFECTIVITY OF ONE GATE POLICY OF HAZARDOUS WASTE MANAGEMENT AT PT. KALTIM PRIMA COAL - Supriyadi, Nanang i -i (EKONOMIA, 2019)
Hazardous waste is one of significant environmental aspect at PT. Kaltim Prima Coal (KPC). Management of hazardous waste has to be complied with PP101/2014. Fail to comply with PP 101/2014, the company will received an administration sanction, and can be escalated to government coercive action, suspend of environmental permit and cancellation of environmental permit. Cancellation of environmental permits means operational permit is not valid, in this condition the company not allowed to be operated. The researched was conducted to confirm effectiveness of KPC ‘s strategy, which implement one gate policy in managing their hazardous waste. The policy effectiveness to meet compliance of PP101/2014 and also added value of this strategy were never been measured. The basic theories of this researchs are operational management and cost budget. The research object only for hazardous waste, the other environmental aspect was excluded. Data of cost hazardous management that will be used only for Sangatta area, Bengalon area was excluded. PERGUB Kaltim nomor 05/2014 dan SK BLH Kaltim nomor 660.2/K.44/2014 and cost comparison will be used as tools for analiys. The data of research were hazardous waste management at PT. KPC and cost spending for hazardous waste in 5 years (2009 – 2014). The result of analysis shown score achieved 14.30% from 15% full score. This score means 14.30/15 or equivalent with 95.33% for aspect of hazardous goods and hazardous waste management, based on PERGUB Kaltim 05/2014 and SK BLH Kaltim 660.2/K.44/2014. Calculation cost comparison during five years (2009-2014) shown that total saving cost is USD 2,132,089.00. Based on this research can be concluded that one gate policy of hazardous management at PT. KPC has been effective to fulfill compliance of PP 101 /2014. Moreover, One gate policy on hazardous waste at KPC was also contributed an added value by saving cost USD 2.132.089 during 5 years (2009-2014)